Penjurian Lomba Kompetensi Siswa SMK Bidang Web Technologies Wilayah Kalimantan Utara - Syaddam; Hadriansa (Jurnal ETAM, 2024)
Vocational High School (SMK) is one of the formal education levels in Indonesia, with strategic potential to fulfill Indonesia's competitive human resources needs and achieve national development goals. Improving Student achievement in Web Technologies is necessary to face the era of digitization and automation. The SMK Student Competency Competition (LKS) competition measures students' abilities in this field at the district level, then progresses to the provincial level and finally reaches the national level. Judges conduct the assessment process according to the National Level SMK LKS 2022 Guidelines. The method used for community service during the judging phase is Assessment Methodology. This competition's organization also involves full support from university academics, primarily through Lecturers who provide new insights as Student judges. Implementing the LKS in North Kalimantan went smoothly in 2022. It received full support from university academics and aimed to allow SMK Students to develop and demonstrate their skills in web technologies.